Hemoglobin promotes Staphylococcus aureus nasal colonization. - Melissa Pynnonen (PLoS Pathogens, 2011)
Staphylococcus aureus nasal colonization is an important risk factor for community and nosocomial infection. Despite the importance of S. aureus to human health, molecular mechanisms and host factors influencing nasal colonization are not well understood. To identify host factors contributing to nasal colonization, we collected human nasal secretions and analyzed their ability to promote S. aureus surface colonization. Some individuals produced secretions possessing the ability to significantly promote S. aureus surface colonization. Nasal secretions pretreated with protease no longer promoted S. aureus surface colonization, suggesting the involvement of protein factors. The major protein components of secretions were identified and subsequent analysis revealed that hemoglobin possessed the ability to promote S. aureus surface colonization. Immunoprecipitation of hemoglobin from nasal secretions resulted in reduced S. aureus surface colonization. Furthermore, exogenously added hemoglobin significantly decreased the inoculum necessary for nasal colonization in a rodent model. Finally, we found that hemoglobin prevented expression of the agr quorum sensing system and that aberrant constitutive expression of the agr effector molecule, RNAIII, resulted in reduced nasal colonization of S. aureus. Collectively our results suggest that the presence of hemoglobin in nasal secretions contributes to S. aureus nasal colonization.